Ellagic Acid: A Dietary-Derived Phenolic Compound for Drug Discovery in Mild Cognitive Impairment - Wang, Wenjun; Wang, Shaohui; Liu, Yue; Wang, Xiaobo; Nie, Jia; Meng, Xianli; Zhang, Yi (Frontiers in Aging Neuroscience, 2022)
Ellagic acid (EA), a naturally occurring polyphenolic compound, is detected in free form or linked to polyols or sugars, constituting hydrolysable tannins or ellagitannins in distinct fruits, nuts, and herbs. Today, a considerable number of botanicals and enriched foods containing EA are commercially available as nutraceuticals and used to prevent mild cognitive impairment (MCI) due to the excellent neuroprotective capacity of EA. Here, this study aims to provide an overview of the physicochemical properties, source, and pharmacokinetics of EA, and to emphasize the importance and mechanisms of EA in the prevention and management of MCI. To date, preclinical studies of EA and its derivatives in various cell lines and animal models have advanced the idea of dietary EA as a feasible agent capable of specifically targeting and improving MCI. The molecular mechanisms of EA and its derivatives to prevent or reduce MCI are mainly through reducing neuroinflammation, oxidative stress, neuronal apoptosis, synaptic dysfunction and loss, and defective mitochondrial functions. Nevertheless, well-designed and correctly large randomized controlled trials in the human population need to be performed to reinforce the scientific facticity on the beneficial effects of EA against MCI. Synchronously, the mechanism of EA against MCI is least provided cynosure and expects more attention from the emerging research community.